Prevalence and risk factors of chronic rhinosinusitis among Chinese: A systematic review and meta-analysis - Zhang, Lan; Zhang, Rong; Pang, Kaiyun; Liao, Jie; Liao, Chao; Tian, Li (Frontiers in Public Health, 2023)
background: Chronic rhinosinusitis (CRS) can be seen in people of all ages. CRS heavily affects the quality of a patient’s daily life, also can cause a tremendous economic burden on patients’ families and society. The prevalence of chronic rhinosinusitis in different countries varies and no systematic review of the prevalence of CRS among Chinese has been published. The aim of this systematic review and meta-analysis is to determine the prevalence of CRS among Chinese and to explore the main risk factors of CRS among Chinese. Methods: Using relevant keywords, data resources including PubMed, Scopus, Web of Science, Google Scholar, Embase, The Cochrane Library, Chinese National Knowledge of Infrastructure (CNKI), WANGFANG, VIP, China Biomedical Literature database (CMB) were searched to obtain literatures reporting the prevalence of and risk factors of CRS among Chinese which were clearly diagnosed with CRS from inception to June 30, 2022. The random/fixed effects model was used for meta-analysis, and the I2 index was employed to assess heterogeneity among studies. The data was analyzed using STATA software version 16.0. The study was registered with PROSPERO, number CRD 42022341877. Result: Totally 12 relevant literatures were qualified for the present systematic review, including 4033 patients. The results showed that the overall prevalence of CRS among Chinese was 10% (95%CI: 0.06-0.13, I2=99.6%, P<0.001). .The prevalence of CRS among Chinese who was never exposed to mouldly or damp environments was 8% (95%CI: 0.08-0.09, I2=0.0%, P=0.351), while the prevalence of CRS among Chinese who was occasionally exposed to mouldly or damp environments was 16% (95%CI: 0.10-0.22, I2=78.9%, P=0.030), the prevalence of CRS among Chinese who was frequently or everyday exposed to mouldly or damp environments was up to 20% (95%CI: 0.15-0.24, I2=0.0%, P=0.558). Conclusion: This meta-analysis shows that the prevalence of CRS among Chinese is relatively high. People who have some risk factors, such as occasional or frequent or everyday exposure to mouldly or damp environments, have a higher prevalence of CRS. We should attach more importance to the risk factors of CRS in clinical practice and disseminate scientific information and carried out education to lower the prevalence of CRS in China.